an investigation into the content of travel blogs including the influence of content on browsers' cognitive states: implications for marketing destinations - li, yuejing (2009)
Marketers have started to capitalize the internet as a communication mechanism successfully in Business to Business and Business to Consumer strategies. Meanwhile, blogging as one special constituent of the internet has significantly gained attention. In addition, travel and tourism as one of the most popular subjects online, it is likely that they will also be prevalent in the blogosphere. The objectives of this study are to evaluate the destination’s attributes (both positively and negatively) by analyzing the contents of the travel blogs; to identify whether the blogs have a considerable impact on browsers and indirectly promote the destination; and to propose recommendations about the use of blogs as a viable destination marketing tool. It is proper to use qualitative research methods to achieve these objectives.